Let n(h) = -h. Let r be n(-5). Let j be 8/((-3)/(6/(-4))). Solve -r = -j*z - z for z.

1

Let h(f) be the second derivative of -f**36 - f. Let o be ((-3)/(-6))/((-1)/10). Let s be h(o). Solve 0 = -s*j + 12 - 2 for j.

2

Let i = 17 + -38. Let x = 21 + i. Solve 6 = 2*n - x*n for n.

3

Suppose -2*x + 25 = 3*x. Suppose -x*y + 7 = -3. Solve -8 = -0*d - y*d for d.

4

Suppose 0 = r + r - 3*m - 7, 6 = 2*r - 2*m. Let s(f) = -f**2 + 2*f + 2. Let x be s®. Let j be (x/4)/(440). Solve -4*u + j*u = 0 for u.

0

Let r be -1*(1 + -2) + 34. Suppose d - r = -0*d. Solve 15 = 4*q + d for q.

-5

Let m be (6*-1)/(9/(-6)). Let s(a) = -a3 + 4*a2 - a + 4. Let i be s(m). Solve 0 = -3*p - i - 9 for p.

-3

Let d be (-7)/(-3)*3/(-1). Let h be 2/d - 111/(-21). Let s be 25 - 820. Solve s = 4*w + w + h for w.

-1

Suppose 5*b + 5 = -3*o, -17 = b - 4*o + 7. Let n = 8 - b. Solve -3 = -3*k + n for k.

5

Let v(n) = 3*n + 5. Let w be v(3). Let i = w + -11. Solve -2*k = -i*k - 1 for k.

-1